Systematic use of long-acting intramuscular progesterone in addition to oral dydrogesterone as luteal phase support for single fresh blastocyst transfer: A pilot study - Simon, Virginie; Robin, Geoffroy; Keller, Laura; Ternynck, Camille; Jonard, Sophie; Robin, Camille; Decanter, Christine; Plouvier, Pauline (Frontiers in Endocrinology, 2022)
Objective The need of luteal support after FET is no longer to be proven. Different routes of progesterone administration are available with interindividual differences in metabolization and serum progesterone levels, the latter being highly correlated with pregnancy and delivery rates. The administration of 2 different routes of progestogen significantly improves success rates in FET. The aim of the current study was to investigate the added value to combine intramuscular administration of progesterone to dydrogesterone in fresh embryo transfer. Methods This is a retrospective study from prospectively collected data. Patient, aged between 18 and 43 years old, had received a fresh blastocyst transfer between January 2021 and June 2021. In the first group, all patients received only oral dydrogesterone 10mg, three times a day, beginning the evening of oocyte retrieval. In the second group, patients received, in addition to dydrogesterone, a weekly intramuscular injection of progesterone started the day of embryo transfer. Primary endpoint was ongoing pregnancy rate. Results 171 fresh single blastocyst transfers have been performed during this period. 82 patients were included in “dydrogesterone only” and 89 patients in “dydrogesterone + IM”. Our two groups were comparable except for body mass index. After adjustment on BMI, our two groups were comparable regarding implantation rate, early pregnancy rate (46.1 versus 54.9, OR 1.44 [0.78; 2.67], p=0.25) miscarriage rate, ongoing pregnancy rate (30.3 versus 43.9, OR 1.85 [0.97; 3.53] p= 0.06). Conclusion Using systematically long acting intramuscular progesterone injection in addition to oral dydrogesterone as luteal phase support seems to have no significant impact on IVF outcomes when a single fresh blastocyst transfer is performed.